2020
DOI: 10.1111/evo.13965
|View full text |Cite
|
Sign up to set email alerts
|

Variable and sexually conflicting selection onSilene stellatafloral traits by a putative moth pollinator selective agent

Abstract: Conflicting selection is an important evolutionary mechanism because it impedes directional evolution and helps to maintain phenotypic variation. It can arise when mutualistic and antagonistic selective agents exert opposing selection on the same trait and when distinct phenotypic optima are favored by different fitness components. In this study, we test for conflicting selection through different sexual functions of the hermaphroditic plant, Silene stellata during its early and late flowering season. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…Importantly, in Zhou et al (2020), we also found conflicting selection pressures exerted on the petal dimensions through the two sexual functions. Remarkably, the floral trait under the strongest conflicting selection (petal length) is also found to have the highest heritability in this paper.…”
Section: Stellatamentioning
confidence: 79%
See 3 more Smart Citations
“…Importantly, in Zhou et al (2020), we also found conflicting selection pressures exerted on the petal dimensions through the two sexual functions. Remarkably, the floral trait under the strongest conflicting selection (petal length) is also found to have the highest heritability in this paper.…”
Section: Stellatamentioning
confidence: 79%
“…The Silene-Hadena interaction is further complicated by a guild of generalist pollinator moths, that are equally effective at pollen transfer (Reynolds et al ., 2012). In a previous study, we found that the parasitic and mutualistic interaction between H. ectypa leads to conflicting selection on the petal dimension through the two sexual functions of S. stellata (Zhou et al ., 2020). Furthermore, the transition between H. ectypa and the copollinating species across the flowering phenology also leads to temporally variable selection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Syndromes are thought to indicate the selective agents that have driven convergent evolution of correlated floral traits (Fenster et al ., 2004). Tests of syndrome hypotheses by analyzing selection on floral traits by specific pollinator groups through male and female function are, however, rare (Reynolds et al ., 2010; Zhou et al ., 2020). Quantitative analyses of syndrome traits for species with known pollination systems (‘observed species’) can be used to identify clustering in trait space (Wilson et al ., 2004; Marten‐Rodriguez et al ., 2009; Armbruster et al ., 2011), and predict pollination systems of species for which traits could be measured, but for which pollinator data are lacking (‘unobserved species’) (Whittall & Hodges, 2007; Navarro‐Perez et al ., 2013).…”
Section: Characterization Of Pollination Systems For Macroevolutionarmentioning
confidence: 99%